2011
DOI: 10.1166/mex.2011.1046
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotube Growth in High Vacuum Using Pt Catalyst in Alcohol Gas Source Method

Abstract: Growth of single-walled carbon nanotubes (SWNTs) was carried out on SiO 2 /Si substrates at 700 C with Pt catalysts using an alcohol gas source method in a high vacuum. Scanning electron microscopy observations and Raman spectroscopy measurements showed the optimal ethanol pressure to be 1 × 10 −4 Pa, which was much smaller than that used in the SWNT growth with a Co catalyst. Raman spectra measured with various excitation wavelengths showed that the G/Si ratios of the SWNTs grown with the Pt catalyst at 1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…At the growth temperature of SWNTs, those residual carbon atoms should be crystallized to hexagonal carbon network, forming carbon nanocaps on the catalyst particle surface. Previously, we discussed that the remarkable reduction of optimal ethanol pressure for Pt catalyst was due to the SWNT growth by a diffusion process of carbon atoms on the catalyst surface without dissolution into Pt [12]. We consider that the small bulk solubility of carbon atoms into Pt leads to the lower ethanol pressure necessary for the Journal of Nanotechnology 5 SWNT growth.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…At the growth temperature of SWNTs, those residual carbon atoms should be crystallized to hexagonal carbon network, forming carbon nanocaps on the catalyst particle surface. Previously, we discussed that the remarkable reduction of optimal ethanol pressure for Pt catalyst was due to the SWNT growth by a diffusion process of carbon atoms on the catalyst surface without dissolution into Pt [12]. We consider that the small bulk solubility of carbon atoms into Pt leads to the lower ethanol pressure necessary for the Journal of Nanotechnology 5 SWNT growth.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, we grew SWNTs using Pt catalysts and showed that SWNTs could be grown even at ambient ethanol pressure of 1 × 10 −4 Pa, while keeping the yield compatible with Co catalysts at 1 × 10 −1 Pa [12,13]. However, it is desirable to reduce the growth temperature to 400…”
Section: Introductionmentioning
confidence: 99%
“…The nominal thickness of Pt was 0.2 nm, which was the optimal thickness to obtain the highest SWNT yield. SWNTs were then grown with the alcohol gas source method in a UHV chamber, a type of cold-wall chemical vapor deposition (CVD) equipment [2]. Ethanol gas was supplied to the substrate surface for 1 h through a stainless steel nozzle with a hole (diameter: 0.5 nm) at the tip.…”
Section: Methodsmentioning
confidence: 99%
“…To fabricate carbon nanotube (CNT) devices in a conventional LSI process, it is desirable to grow SWNTs at low temperature under high vacuum. So far, we reported that, by using the Pt catalysts, SWNTs could be grown at 700ºC under an ethanol pressure of 10 -3 Pa, while keeping the yield comparable with that grown with Co catalyst at 10 -1 Pa [2,3]. For application to the fabrication of CNT devices compatible with present CMOS, it is important to reduce the growth temperature to below 500ºC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, we have reported SWCNT growth using Co catalysts in an alcohol gas source method, a type of cold-wall chemical vapor deposition (CVD) and succeeded in SWCNT growth at 400ºC by optimizing the growth condition [2]. Recently, by using Pt as catalysts, we attained SWCNT growth under an ethanol pressure of 10 -3 Pa, while the SWCNT yield was larger than those grown from Co catalysts at the growth temperature of 700ºC [3].…”
Section: Introductionmentioning
confidence: 99%